Educational goals, parenting practices and adolescents' academic achievement - Baharudin, Rozumah; Hong, Chi Yee; Lim, Sin Jing; Zulkefly, Nor Sheereen (Canadian Center of Science and Education, 2010)
The present study examined linkages between educational goals, parenting practices (school involvement and monitoring) of single-mothers and single-fathers, and the academic achievement of their school-going adolescents. Additionally, it sought to examine the differences in educational goals and parenting practices between the single fathers and mothers, as well the parents’ differential treatments toward their male and female adolescents. Through Single Mother Associations, we recruited 60 single mothers and snowball 30 single fathers for the study. We found that the parents differ only in terms of educational goals where single fathers had significantly lower goals compared to single mothers. In zero order correlational analyses, we discovered positive relationships between (1) parenting practices and academic achievement of adolescents from both families; (2) fathers’ educational goals and their monitoring behaviors; and (3) mothers’ educational goals and their school involvement, and monitoring behaviors. Findings from this study accentuate the importance of an active educational socialization process in diverse family settings to promote adolescents’ educational success.